7(3x+9)-6(2x+5)=

Simple and best practice solution for 7(3x+9)-6(2x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x+9)-6(2x+5)= equation:


Simplifying
7(3x + 9) + -6(2x + 5) = 0

Reorder the terms:
7(9 + 3x) + -6(2x + 5) = 0
(9 * 7 + 3x * 7) + -6(2x + 5) = 0
(63 + 21x) + -6(2x + 5) = 0

Reorder the terms:
63 + 21x + -6(5 + 2x) = 0
63 + 21x + (5 * -6 + 2x * -6) = 0
63 + 21x + (-30 + -12x) = 0

Reorder the terms:
63 + -30 + 21x + -12x = 0

Combine like terms: 63 + -30 = 33
33 + 21x + -12x = 0

Combine like terms: 21x + -12x = 9x
33 + 9x = 0

Solving
33 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-33' to each side of the equation.
33 + -33 + 9x = 0 + -33

Combine like terms: 33 + -33 = 0
0 + 9x = 0 + -33
9x = 0 + -33

Combine like terms: 0 + -33 = -33
9x = -33

Divide each side by '9'.
x = -3.666666667

Simplifying
x = -3.666666667

See similar equations:

| 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 | | 6r-6r=-5+r | | A(A-12)-15=30 | | 2y-5+7=-32 | | 2x+10-x+55=90 | | 4.5a=24+2.5a | | b-19=10 | | 13=-3+x | | P=ab+c | | 100/80*78000= | | 7+2(-3n-7)=-4n-21 | | 1x+2=1x+29 | | -3f+19=14 | | 2x-61=x+3 | | 12x+48=22 | | N+15=31 | | 100/20/78000= | | c^2+5+4=0 | | 6=2*.5+5 | | 4t=33 | | 4t=30 | | 4z=-6z-30 | | -4a-(3a-2)=-12 | | .75x+8y=24 | | -4x+9+5-2x+5-2x= | | 50-3x+80=7x | | 8x+4y=14 | | 20/100*78000= | | -4x+9+5-2x+5-2x=X |

Equations solver categories